Spirulina as functional food: insights into cultivation, production, and health benefits - Verma, Akant Kumar; Dewangan, Kajal; Daunday, Leena; Naurange, Kriti; Verma, Kishan; Bhiaram, Monika (Journal of Applied Pharmaceutical Research, 2024)
Background: Spirulina (Arthrospira platensis), a filamentous cyanobacterium, is renowned as a superfood due to its rich nutritional composition, including proteins, carbohydrates, essential fatty acids, vitamins, minerals, and phytochemicals. Historically consumed by the Aztecs and the Kanembu people near Lake Chad, it gained renewed interest in the 20th century as a potential astronaut food. Objective: This review aims to trace Spirulina's evolution from an ancient dietary staple to a modern superfood, emphasizing its immune support, antioxidant properties, and essential nutrients. It also highlights ongoing research on Spirulina's potential to address various health concerns and nutritional needs. Method: The review adopts a comprehensive approach to evaluate Spirulina's pharmacological and therapeutic potential. It systematically examines existing literature, research studies, and clinical trials on Spirulina's health benefits and applications, focusing on its ability to combat malnutrition, boost economies, and offer novel therapeutic interventions. Results: Spirulina is identified as a valuable natural resource with significant potential in nutrition and medicine. The review underscores its pharmacological and therapeutic attributes, particularly in addressing malnutrition and contributing to economic development. Conclusion: Spirulina's role as an effective medicinal resource is discussed, highlighting its implications for novel therapeutic interventions. Overall, the findings underscore Spirulina's nutritional significance, enduring appeal, and promising role in tackling contemporary health challenges.